Common Fixed Points of Set –Valued Mappings on Partial b - Metric Spaces - Khaleel, Liqaa Jameel (Iraqi Journal of Science, 2024)
In this work, the Banach contraction principle is generalized to a new formula. Then, it is used to give the  guarantee conditions for the existence of common fixed point for set valued mappings defined on complete partial b-metric spaces. In addition, some results in connection with  the existence of a  fixed point for a set-valued mapping defined on a partial b-metric space are given. Some  examples are established to illustrate  our results.